An Island Called Home : Returning to Jewish Cuba - Behar, Ruth (Book collections on Project MUSE., 2007)
Yiddish-speaking Jews thought Cuba was supposed to be a mere layover on the journey to the United States when they arrived in the island country in the 1920s. They even called it "Hotel Cuba." But then the years passed, and the many Jews who came there from Turkey, Poland, and war-torn Europe stayed in Cuba. The beloved island ceased to be a hotel, and Cuba eventually became "home." But after Fidel Castro came to power in 1959, the majority of the Jews opposed his communist regime and left in a mass exodus. Though they remade their lives in the United States, they mourned the loss of the Jewis.